Barberry plays an active role as an alternate host of Puccinia graminis in Spain. (9th March 2022) - Villegas, Dolors; Bartaula, Radhika; Cantero‐Martínez, Carlos; Luster, Douglas; Szabo, Les; Olivera, Pablo; Berlin, Anna; Rodriguez‐Algaba, Julian; Hovmøller, Mogens S.; McIntosh, Robert; Jin, Yue
Abstract: Stem rust, caused by Puccinia graminis, is a destructive group of diseases. The pathogen uses Berberis species as alternate hosts to complete its life cycle. B . vulgaris and the endemic species B. hispanica and B. garciae are present in Spain. The objective of this study was to investigate the functionality of the indigenous barberry as alternate hosts. Field surveys were conducted in 2018 and 2019 in Huesca, Teruel and Albacete provinces of Spain. Aecial samples on barberry were analysed via infection assays and DNA analysis. B . garciae was predominant in Huesca and Teruel provinces, often found in the field margins of cereal crops. Aecial infections on B . garciae were observed in May and uredinial infections on cereal crops in June. Scattered B . hispanica bushes were occasionally found near cereal crops in Albacete, where aecial infections on B . hispanica were observed in June when most cereal crops were mature. Infection assays using aeciospores resulted in stem rust infections on susceptible genotypes of wheat, barley, rye and oat, indicating the presence of the sexual cycle for P . graminis f. sp. tritici, f. sp. secalis and f. sp. avenae . Sequence analyses from aecial samples supported this finding as well as the presence of Puccinia brachypodii . This study provides the first evidence that indigenous Berberis species play an active role in the sexual cycle of P . graminis under natural conditions in Spain. Abstract : Plants of indigenous Berberis spp. were frequently found growing near cereal crop fields in some areas of Spain and aeciospores from these barberries infected wheat, barley, rye and oats.